Crushing behavior of multi-layer metal lattice panel fabricated by selective laser melting. (September 2018) - Li, Chuanlei; Lei, Hongshuai; Liu, Yabo; Zhang, Xiaoyu; Xiong, Jian; Zhou, Hao; Fang, Daining
Highlights: Effects of layer and cell numbers on the quasi-static compressive response of BCCZ lattice sandwich panel are studied. An analytical model is proposed to predict the compressive properties of the multi-layer lattice panels. Multi-layer lattice panel exhibits distinctive deformation modes with multiple peak stress under uniaxial compression. The boundary effect of lattice core panel with finite width is discussed through finite element and theoretical methods. Abstract: With the development of the additive manufacturing technique, periodic lattice structures have received increased attention due to their excellent stiffness-to-weight ratio. In this study, the effects of layer and cell numbers on the quasi-static compressive responses of a lattice sandwich panel are systematically investigated through theoretical modeling, experimental testing, and finite element method. A theoretical model is proposed to predict the compressive modulus and initial crushing strength of the multi-layer lattice panels with body-centered cubic with vertical strut (BCCZ) cells. A series of BCCZ panels with various layers is fabricated by selective laser melting (SLM) using AlSi10Mg. The deformation mode and failure mechanism of the structures are analyzed based on the compressive results. Finite element analysis (FEA) is conducted, and its results are compared with the experimental and theoretical results. Modulus and strength decrease remarkably with the increase in layer number ascribing to the weak boundary of cells close to the edge. Layer-by-layer progressive damage is the main failure mode in the multi-layer panel, and multiple peak stresses are observed. The theoretical prediction results are in line with the experimental and FEA results. This work can provide guidance in the design of lightweight lattice structures. Graphical abstract : Image, graphical abstract